Análisis del Gasto del Bolsillo en el Servicio Dental de los Afiliados al SIS de Lima Metropolitana según Enaho, 2018 - Diaz-Mujica, Juana Yris (2021)
Objectives: To estimate the Out-of-Pocket Expense in the Dental Service of the Members of the Metropolitan Lima SIS according to Enaho 2018. Materials and methods: Quantitative study, descriptive approach, of non-experimental, cross-sectional and retrospective design. The technique was the collection of data through the Registration Form taking secondary data from the “National Household Survey on Housing Conditions and Poverty, Enaho, 2018”, the sample was of 14,874 people who have been treated in the dental service in the year 2018. Results: At intervals of 9.705059 and 19.95492 as lower and upper limits than a standard deviation of 2.610325, the pocket expenditure was 14.82999; Regarding spending by sex, on average, that of women was 19.46143 and of men 9.914876; spending according to age indicates that the 65 to 69 age group spends an average of 40.03425 soles; spending by educational level indicates that those with initial level spend 40.24546; and in terms of poverty level, the extreme poor have expenses of 0.000 while the non-extreme poor 2.850577 Conclusions: It concluded that the out-of-pocket expenses for the dental service in SIS is 14.80 soles average, in  Metropolitan Lima for SIS affiliates.